Thermal interface material and preparation method thereof

Through the treatment of graphite heat-homogenized film and carbonizable polymer solution, a high thermal interface material is formed, which solves the problem of insufficient thermal conductivity in the prior art, reduces costs, and achieves the improvement of thermal conductivity and thickness. Controllability.

CN119263831APending Publication Date: 2025-01-07SHANGHAI HUAO NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310818942.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-05
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The thermal conductivity of existing thermal interface materials is difficult to exceed 70W*m-1K-1, and the cost is high while achieving high vertical heat conductivity.

Method used

The graphite-based homogenizing film was cut into a heat-homogenizing film short filaments mixed with a carbonizable polymer solution. After low-temperature pretreatment, medium-temperature carbonization and high-temperature graphitization, a square block with a density of 0.1-1.0 g/cm3 was formed. It is cut into a thermal interface material with a thickness of 0.01 mm-10 mm.

Benefits of technology

The thermal conductivity of thermal interface materials is achieved at least 90W*m-1K-1, and the cost is reduced and the thickness is controllable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004322844270000011
    Figure HDA0004322844270000011
  • Figure HDA0004322844270000012
    Figure HDA0004322844270000012
  • Figure HDA0004322844270000021
    Figure HDA0004322844270000021
Patent Text Reader

Abstract

The invention provides a thermal interface material and a preparation method thereof, and relates to the technical field of graphene materials. Comprising the following steps: cutting a graphite soaking film into soaking film short wires according to preset parameter conditions; mixing the soaking film short filaments with a carbonizable polymer solution to obtain a mixed solution; guiding the mixed solution into a preset vertically arranged mold until the mixed solution is solidified; sequentially carrying out low-temperature pretreatment, medium-temperature carbonization treatment and high-temperature graphitization treatment on the cured mixed solution to obtain a square block with the density of 0.1-1.0 g / cm < 3 >; and the graphitized square block is cut into the thermal interface material with the thickness ranging from 0.01 mm to 10 mm. The technical problem that the thermal conductivity of the oriented thermal interface material is difficult to break through 70W * m <-1 > K <-1 > is solved, the thickness of the prepared thermal interface material is controllable, the thermal conductivity can reach more than 90W * m <-1 > K <-1 >, and meanwhile, the cost can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of graphene materials, and in particular to a thermal interface material and a preparation method thereof. Background Art

[0002] With the rapid development of power density integration, miniaturization and intelligence of electronic devices, high-performance thermal interface materials are becoming an increasingly urgent need for thermal management of electronic devices.

[0003] Traditional thermal interface materials are prepared by randomly blending high thermal conductive fillers with polymer matrices. When the filling content exceeds 50 vol%, the thermal conductivity is less than 12 W*m -1 K -1 . Regulating the vertical orientation of fillers is an important method to improve the thermal conductivity of thermal interface materials. High thermal conductivity two-dimensional nanofillers, such as few-layer graphene, boron nitride, carbon fiber, etc., have been widely used as building blocks to construct vertically oriented thermal conductive networks. Common orientation regulation methods include electric field orientation, magnetic field orientation, oriented ice template method, flow orientation, etc. However, the thermal conductivity of oriented thermal interface materials is difficult to exceed 70W*m -1 K -1 , and how to achieve it under the condition of high vertical thermal conductivity and relatively low cost will face different huge challenges; therefore, the present invention proposes a thermal interface material and a preparation method thereof to at least partially solve the problems that may exist in the prior art. Summary of the invention

[0004] The purpose of the present invention is to provide a thermal interface material and a preparation method thereof, which can provide a solution to the shortcomings of the prior art and solve the problem that the thermal conductivity of the oriented thermal interface material in the prior art is difficult to exceed 70W*m -1 K -1 The technical problem of achieving the thermal interface material prepared is not only controllable in thickness, but also has a thermal conductivity of up to 90W*m -1 K -1 The above, while also reducing costs.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0006] A method for preparing a thermal interface material, comprising:

[0007] Cutting the graphite heat-spreading film into short heat-spreading film filaments according to predetermined parameter conditions;

[0008] Mixing the short filaments of the heat-spreading film with a carbonizable polymer solution to obtain a mixed solution;

[0009] Introducing the mixed solution into a preset vertically arranged wooden mold until the mixed solution solidifies to obtain a mixed solution solidified product;

[0010] The mixed liquid solidified material is sequentially subjected to low temperature pretreatment, medium temperature carbonization treatment and high temperature graphitization treatment to obtain a density of 0.1-1.0 g / cm 3 square blocks;

[0011] The graphitized square block is cut into thermal interface materials with a thickness between 0.01 mm and 10 mm.

[0012] Further, in the present invention, the above-mentioned cutting of the graphite-based heat-spreading film into short heat-spreading film filaments according to predetermined parameter conditions includes:

[0013] Selecting one or more mixtures of artificial graphite film, graphene soaking film, and natural graphite film as the graphite soaking film;

[0014] Cut the graphite heat spreader film into heat spreader film wires with a width of 10um-1000um and a length of 5-5000cm;

[0015] The heat-spreading film wire is cut into short heat-spreading film wires with a length of 0.5 cm-5 cm.

[0016] Furthermore, in the present invention, the above-mentioned artificial graphite film, graphene soaking film, natural graphite film or one or more mixtures thereof are selected as the graphite soaking film, including:

[0017] One or more mixtures of artificial graphite film, graphene heat spreader film, and natural graphite film with a heat spreader thickness of 5-100um and a density of 0.4-2.26g / cm2 are selected as the graphite heat spreader film.

[0018] Further, in the present invention, the above-mentioned mixing of the heat-spreading film short filaments with the carbonizable polymer solution to obtain a mixed solution comprises:

[0019] The short filaments of the heat-spreading film are added into the polymer solution and suspended in the polymer solution to form a carbonizable and graphitizable polymer mixed solution.

[0020] Furthermore, in the present invention, the above-mentioned heat-dissipating film filaments are added to the polymer solution and suspended in the polymer solution to form a carbonizable and graphitizable polymer mixed solution, including: mixing the heat-dissipating film filaments in a polymer solution or multiple mixed polymer solutions in a polyimide solution and a polyacrylonitrile solution to form a carbonizable and graphitizable polymer mixed solution.

[0021] Furthermore, in the present invention, the step of introducing the mixed solution into a preset vertically arranged mold until the mixed solution is solidified to obtain a mixed solution solidified product comprises:

[0022] The mixed solution is introduced into a vertically arranged mold with a cavity size of 10-100um and a depth of 10mm-5000mm until the mixed solution is solidified, wherein the width and length of the mold are both between 10mm-10000mm.

[0023] Furthermore, in the present invention, the mixed solution is introduced into a preset vertically arranged mold until the mixed solution is solidified to obtain a mixed solution solidified product, comprising:

[0024] The mixed solution is introduced into a vertically arranged wooden mold, or a carbonized and graphitized polymer mold, or a graphite mold, until the mixed solution is solidified to obtain a mixed solution solidified product.

[0025] Furthermore, in the present invention, the mixed liquid solidified material is subjected to low temperature pretreatment, medium temperature carbonization treatment and high temperature graphitization treatment in sequence to obtain a density of 0.1-1.0 g / cm 3 A square block, including:

[0026] The mixed solution after curing is subjected to reduction pretreatment in a low temperature environment of 200-600° C. until it is reduced from the wooden mold; wherein the heating rate of the reduction pretreatment is controlled at 0.05° C. / min-1° C. / min, and the holding time is controlled at 30min-360min;

[0027] The mixed solution after reduction pretreatment is subjected to carbonization treatment in a medium temperature environment of 600-1600° C. to obtain a graphite block; wherein the heating rate of the carbonization treatment is controlled at 1° C. / min-5° C. / min, and the holding time is controlled at 30min-360min;

[0028] The graphite block is subjected to graphitization treatment in a high temperature environment of 2000°C-3000°C to obtain a density of 0.1-1.0 g / cm 3 , and inside it is a square block with a vertically arranged array of heat-spreading membrane wires.

[0029] Furthermore, in the present invention, the square block after graphitization is cut into thermal interface materials with a thickness between 0.01 mm and 10 mm, comprising:

[0030] The graphitized blocks are cut vertically to obtain thermal interface materials with a thickness between 0.01 mm and 10 mm.

[0031] Furthermore, in the present invention, the graphitized blocks are vertically cut into thermal interface materials with a thickness between 0.01 mm and 10 mm, comprising:

[0032] The graphitized square block with a vertically arranged heat-dissipating membrane wire array is cut vertically to obtain a square block with a thickness of 0.01 mm to 10 mm and a density of 0.1 to 1.0 g / cm 3 The vertical thermal conductivity is 90-150W*m -1 K -1 Thermal interface materials.

[0033] A thermal interface material, wherein the density of the thermal interface material is 0.1-1.0 g / cm 3 , thickness is 0.01mm-10mm, and its vertical thermal conductivity can be controlled to 90-150W*m -1 K -1 , which is prepared by the above preparation method.

[0034] The present invention has at least the following advantages or beneficial effects:

[0035] The method comprises the following steps: cutting a graphite-based heat-spreading film into short heat-spreading film filaments according to predetermined parameter conditions; mixing the short heat-spreading film filaments with a carbonizable polymer solution to obtain a mixed solution; introducing the mixed solution into a preset vertically arranged wooden mold until the mixed solution solidifies to obtain a mixed solution solid; sequentially performing a low-temperature pretreatment, a medium-temperature carbonization treatment and a high-temperature graphitization treatment on the mixed solution solid to obtain a density of 0.1-1.0 g / cm 3 The graphitized square block is cut into thermal interface materials with a thickness of 0.01 mm to 10 mm. The thermal conductivity of the oriented thermal interface material is difficult to exceed 70 W*m -1 K -1 The technical problem of achieving the thermal interface material prepared is not only controllable in thickness, but also has a thermal conductivity of up to 90W*m -1 K -1 The above, while also reducing costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0037] Figure 1 A flow chart of steps of a method for preparing a thermal interface material provided by one embodiment of the present invention;

[0038] Figure 2 A SEM image of a vertically arranged wood structure of a wood mold provided by an embodiment of the present invention;

[0039] Figure 3 A schematic diagram of pouring slurry into a mold when introducing the mixed solution into a vertically arranged wooden mold provided in one embodiment of the present invention. DETAILED DESCRIPTION

[0040] In order to make the objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] Example 1

[0042] Please refer to Figure 1 , shows a flow chart of the steps of a method for preparing a thermal interface material provided by this embodiment, which includes the following steps:

[0043] Step S101, cutting the graphite soaking film into soaking film short filaments according to predetermined parameter conditions;

[0044] Step S102, mixing the short filaments of the heat-spreading film with a carbonizable polymer solution to obtain a mixed solution;

[0045] Step S103, introducing the mixed solution into a preset vertically arranged wooden mold until the mixed solution solidifies to obtain a mixed solution solidified product;

[0046] Step S104: subjecting the solidified product of the mixed liquid to low-temperature pretreatment, medium-temperature carbonization treatment and high-temperature graphitization treatment in sequence to obtain a solidified product having a density of 0.1-1.0 g / cm 3 square blocks;

[0047] Step S105: cutting the graphitized square block into thermal interface materials with a thickness between 0.01 mm and 10 mm.

[0048] The above thermal interface material preparation method solves the problem of high thermal conductivity thermal interface material and breaks through 70W*m -1 K -1 Limitation, and reduce costs, to achieve vertical thermal conductivity of 90W*m -1 K -1 The above also achieves the effect that the thickness of the thermal interface material made by the above method can be controlled.

[0049] As a preferred implementation, the specific process of the above step S101 "cutting the graphite-based heat-spreading film into short heat-spreading film filaments according to predetermined parameter conditions" includes: selecting one or more mixtures of artificial graphite film, graphene heat-spreading film, and natural graphite film as the graphite-based heat-spreading film;

[0050] Cut the graphite heat spreader film into heat spreader film wires with a width of 10um-1000um and a length of 5-5000cm;

[0051] The heat-spreading film wire is cut into short heat-spreading film wires with a length of 0.5 cm-5 cm.

[0052] It should be noted that graphene-like thermal interface material is a material with high thermal conductivity and low electrical conductivity. The film material is composed of many layers of graphene sheets and has excellent thermal conductivity. It can quickly transfer heat to adjacent devices or materials, thereby improving the heat dissipation efficiency of the system.

[0053] As a preferred embodiment, the specific process of "mixing the heat-spreading film filaments with a carbonizable polymer solution to obtain a mixed solution" as described in the above step S102 includes adding the heat-spreading film filaments to the polymer solution and suspending them in the polymer solution to form a carbonizable and graphitizable polymer mixed solution.

[0054] As a preferred embodiment, the specific process of "introducing the mixed solution into a preset vertically arranged wooden mold until the mixed solution is solidified to obtain a mixed solution solidified product" as described in step S103 above, introducing the mixed solution into a vertically arranged wooden mold, or a carbonizable graphitizable polymer mold, or a graphite mold, comprises: introducing the mixed solution into a vertically arranged wooden mold, or a carbonizable graphitizable polymer mold, or a graphite mold, Figure 2 The wooden mold shown in the figure has a cavity size of 10-100um and a depth of 10mm-5000mm in a vertically arranged wooden mold until the mixed solution is solidified, wherein, as Figure 3 The slurry is poured into a vertically arranged wooden mold, wherein the width and length of the wooden mold are between 30 mm and 10000 mm.

[0055] As a preferred embodiment, as described in step S104 above, "the mixed liquid solidified material is subjected to low temperature pretreatment, medium temperature carbonization treatment and high temperature graphitization treatment in sequence to obtain a density of 0.1-1.0 g / cm 3The specific process of "forming a square block of a wooden mold" includes performing a reduction pretreatment on the solidified mixed solution in a low temperature environment of 200-600°C until it is restored from the wooden mold; wherein the heating rate of the reduction pretreatment is controlled at 0.05°C / min-1°C / min, and the insulation time is controlled at 30min-360min;

[0056] The mixed solution after reduction pretreatment is subjected to carbonization treatment in a medium temperature environment of 600-1600° C. to obtain a graphite block; wherein the heating rate of the carbonization treatment is controlled at 1° C. / min-5° C. / min, and the holding time is controlled at 30min-360min;

[0057] The graphite block is subjected to graphitization treatment in a high temperature environment of 2000°C-3000°C to obtain a density of 0.1-1.0 g / cm 3 , and inside it is a square block with a vertically arranged array of heat-spreading membrane wires.

[0058] As a preferred implementation manner, the specific process of "cutting the graphitized square block into thermal interface materials with a thickness between 0.01mm-10mm" as described in the above step S105 includes vertically cutting the graphitized block to obtain a thermal interface material with a thickness between 0.01mm-10mm.

[0059] In a specific embodiment, one or more mixtures of artificial graphite film, graphene heat spreader film, and natural graphite film are selected as the graphite heat spreader film. For example, a mixture of 10 μm thick and 0.4 g / cm 3 The artificial graphite heat spreader is cut into heat spreader wires with a length of 50cm and a width of 500um;

[0060] The artificial graphite heat-spreading film wire is cut into short heat-spreading film wires with a length of 0.5 cm;

[0061] The short filaments of the heat-spreading film made of the artificial graphite film are mixed in a polymer solution of polyimide to form a carbonizable and graphitizable polymer mixed solution;

[0062] Pour the polymer mixed solution into a vertically arranged wooden mold; the cavity size in the wooden mold is 10um, the dimensions are 5000mm in depth, 1000mm in width and 1000mm in length;

[0063] The mixed solution after curing is subjected to reduction pretreatment in a low temperature environment of 500-600°C until it is restored from the wooden mold; wherein the heating rate of the reduction pretreatment is controlled at 0.05°C / min-1°C / min, and the holding time is controlled at 30min-360min. For example, the mold in the mold of the cured mixed solution is restored, the low temperature pretreatment temperature is treated at 600°C, the heating rate is controlled at 5°C / min, and the holding time is controlled at 360min.

[0064] The product after low-temperature curing and reduction is subjected to carbonization treatment, with the temperature controlled at 1600°C, the heating rate controlled at 1°C / min, and the insulation time controlled at 60min.

[0065] The carbonized product is graphitized at high temperature to form a square block with a vertically arranged heat-spreading membrane wire array. The temperature is controlled at 3200°C, the heating rate is controlled at 5°C / min, and the insulation time is controlled at 30min.

[0066] The graphitized square block with a certain density is cut into a thermal interface material with a thickness of 2 mm; its density is 0.8 g / cm 3 According to the calculation, the vertical thermal conductivity of the thermal interface material obtained by the above method is 150W*m -1 K -1 .

[0067] The thermal interface material prepared by the method of the present application can not only break through the highest vertical thermal conductivity of the prior art which can only reach 70W*m -1 K -1 The limitation of the thermal interface material can be eliminated, and the vertical thermal conductivity can be more than twice the current one. At the same time, the thickness of the cut thermal interface material can be controlled by the above method to meet the market demand for thermal interface materials of different thicknesses.

[0068] Example 2

[0069] This embodiment provides a method for preparing a thermal interface material, which comprises the following steps:

[0070] Selecting one or more mixtures of artificial graphite film, graphene soaking film, and natural graphite film as the graphite soaking film;

[0071] Cut the graphite heat spreader film into heat spreader film wires with a width of 10um-1000um and a length of 5-5000cm;

[0072] Cut the above-mentioned heat-spreading film wire into short heat-spreading film wires with a length of 0.5 cm-5 cm;

[0073] The short filaments of the heat-spreading film are mixed in a carbonizable polymer solution to form a mixed solution;

[0074] Introducing the mixed solution into a preset vertically arranged wooden mold until the mixed solution solidifies to obtain a mixed solution solidified product;

[0075] The solidified product of the mixed liquid is sequentially subjected to low temperature pretreatment, medium temperature carbonization treatment and high temperature graphitization treatment to obtain a density of 0.1-1.0 g / cm 3 square blocks;

[0076] The graphitized square block is cut into thermal interface materials with a thickness between 0.01 mm and 10 mm.

[0077] As a preferred implementation manner, the selection of one or more mixtures of artificial graphite film, graphene thermal diffusion film, and natural graphite film as the graphite thermal diffusion film includes: selecting one or more mixtures of artificial graphite film, graphene thermal diffusion film, and natural graphite film with a thermal film thickness of mainly 5-100um and a density of 0.4-2.26g / cm2 as the graphite thermal diffusion film.

[0078] As a preferred embodiment, the mixed solution is introduced into a preset vertically arranged wooden mold until the mixed solution is solidified to obtain a mixed solution solidified product, including introducing the mixed solution into a vertically arranged wooden mold with a cavity size of 10-100um and a depth of 10mm-1000mm or 1000mm-5000mm until the mixed solution is solidified, wherein the width of the wooden mold is 10mm-30mm and the length is between 30mm-10000mm;

[0079] As a preferred embodiment, the solidified mixed solution is subjected to reduction pretreatment in a low temperature environment of 200-500°C until it is restored from the wooden mold; wherein the heating rate of the reduction pretreatment is controlled at 0.05°C / min-1°C / min, and the holding time is controlled at 30min-360min;

[0080] As a preferred embodiment, the mixed solution after reduction pretreatment is carbonized in a medium temperature environment of 600-1300°C or 1300-1600°C to obtain a graphite block; wherein the heating rate of the carbonization treatment is controlled at 1°C / min, and the holding time is controlled at 120min;

[0081] The graphite block is subjected to graphitization treatment in a high temperature environment of 2000°C-2800°C to obtain a density of 0.1-1.0 g / cm 3, and inside it is a square block with a vertically arranged array of heat-spreading membrane wires.

[0082] As a preferred embodiment, the square block with the vertically arranged heat-spreading membrane wire array after graphitization is vertically cut to obtain a square block with a thickness of 1 mm to 2 mm and a density of 0.8 to 1.0 g / cm 3 The vertical thermal conductivity is between 12-150W*m -1 K -1 Thermal interface materials.

[0083] In a specific embodiment, a mixture of one or more graphene heat spreader films or natural graphite films is selected as the graphite heat spreader film. Specifically, a heat spreader film with a thickness of 70 um and a density of 1.0 g / cm 3 The natural graphite heat spreader is cut into heat spreader wires with a length of 5cm and a width of 100um;

[0084] Cut the natural graphite heat-spreading membrane wire into short wires with a length of 5 cm;

[0085] The natural graphite film filaments are mixed in a polyacrylonitrile solution to form a polymer solution;

[0086] Pour the polymer mixed solution into a vertically arranged wooden mold, wherein the cavity size in the wooden mold is 10um, the dimension depth is 5000mm, the width is 10mm, and the length is 1000mm;

[0087] The mold in the solidified mixed solution mold is restored, the low-temperature pretreatment temperature is treated at 600°C, the heating rate is controlled at 5°C / min, and the holding time is controlled at 360min;

[0088] The product after low-temperature solidification and reduction is subjected to carbonization treatment, with the temperature controlled at 1300°C, the heating rate controlled at 1°C / min, and the insulation time controlled at 120min.

[0089] The carbonized graphite block is graphitized at high temperature to form a square block with a vertically arranged heat-spreading membrane wire array. The temperature is controlled at 1300°C, the heating rate is controlled at 10°C / min, and the insulation time is controlled at 60min.

[0090] The graphitized square block with a certain density is cut into thermal interface materials with a thickness of 1 mm; its density is 0.8 g / cm 3 According to the calculation, the vertical thermal conductivity of the thermal interface material obtained by the above method is 120W*m -1 K -1 .

[0091] Example 3

[0092] A method for preparing a thermal interface material, comprising: selecting a natural graphite film as the graphite-based heat-spreading film;

[0093] Cut the graphite heat spreader film into heat spreader film wires with a width of 10um-1000um and a length of 5-5000cm;

[0094] Cut the above-mentioned heat-spreading film wire into short heat-spreading film wires with a length of 0.5 cm-5 cm;

[0095] Mixing the short filaments of the heat-spreading film with a polymer solution or a plurality of mixed polymer solutions in a polyimide solution or a polyacrylonitrile solution to form a carbonizable and graphitizable polymer mixed solution;

[0096] The mixed solution is introduced into a vertically arranged wooden mold with a cavity size of 10-100um and a depth of 10mm-5000mm until the mixed solution is solidified, wherein the width and length of the wooden mold are both between 30mm-10000mm;

[0097] The solidified mixed solution is subjected to reduction pretreatment in a low temperature environment of 200-500° C. until it is reduced from the wooden mold; wherein the heating rate of the reduction pretreatment is controlled at 0.05° C. / min-1° C. / min, and the holding time is controlled at 30 min-360 min;

[0098] The mixed solution after reduction pretreatment is subjected to carbonization treatment in a medium temperature environment of 600-1600° C. to obtain a graphite block; wherein the heating rate of the carbonization treatment is controlled at 1° C. / min-5° C. / min, and the holding time is controlled at 30min-360min;

[0099] The graphite block is subjected to graphitization treatment in a high temperature environment of 2000°C-3000°C to obtain a density of 0.1-1.0 g / cm 3 , and inside it is a square block with a vertically arranged array of heat-spreading film wires;

[0100] The graphitized square block is cut into thermal interface materials with a thickness between 0.01 mm and 10 mm.

[0101] In one embodiment, the thickness is 100 um and the density is 2.26 g / cm 3 The graphene heat spreader film is cut into heat spreader film wires with a length of 5000cm and a width of 1000um;

[0102] Cut the graphene heat-spreading film filament into short heat-spreading film filaments with a length of 5 cm;

[0103] Mixing the graphene heat-spreading film short filaments in a polymer solution of polyimide to form a polymer solution;

[0104] Pour the polymer mixed solution into a vertically arranged wooden mold, wherein the cavity size in the wooden mold is 10um, the size depth is 10mm, the width is 100mm, and the length is 1000mm;

[0105] The mold in the solidified mixed solution mold is restored, the low-temperature pretreatment temperature is treated at 200°C, the heating rate is controlled at 0.05°C / min, and the insulation time is controlled at 30min.

[0106] The product after low-temperature curing and reduction is subjected to carbonization treatment, with the temperature controlled at 600°C, the heating rate controlled at 1°C / min, and the insulation time controlled at 360min.

[0107] The carbonized graphite block is graphitized at high temperature to form a square block with a vertically arranged heat-spreading membrane wire array. The temperature is controlled at 2000°C, the heating rate is controlled at 5°C / min, and the insulation time is controlled at 30min.

[0108] The graphitized square block with a certain density is cut into thermal interface materials with a thickness of 0.2mm. The density is 0.1g / cm 3 According to the calculation, the vertical thermal conductivity of the thermal interface material is 90W*m -1 K -1 .

[0109] Example 4

[0110] This embodiment provides a thermal interface material, which is prepared by the preparation method in any of the above embodiments. The thermal interface material has a density of 0.1-1.0 g / cm 3 , thickness is 0.01mm-10mm, the final vertical thermal conductivity can be controlled to 90-150W*m -1 K -1 .

[0111] The present invention not only breaks through the thermal interface material prepared in the prior art, but also the thermal conductivity of which cannot reach 70W*m -1 K -1 The above problems can be solved, and the thickness of the material can be controlled to meet different market demands. At the same time, the reagents used in its preparation, such as polyimide solution and polyacrylonitrile solution, and the mold is a wooden mold, which has low cost and further saves costs, which has a driving effect on the development of the field of graphene materials.

[0112] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

[0113] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0114] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the embodiments of the present invention.

[0115] Finally, it should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or terminal device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or terminal device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or terminal device including the elements.

[0116] The thermal interface material and preparation method thereof provided by the present invention are introduced in detail above. Specific examples are used herein to illustrate the principle and implementation mode of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation mode and application scope. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A method for preparing a thermal interface material, characterized in that: include: Cutting the graphite heat-spreading film into short heat-spreading film filaments according to predetermined parameter conditions; Mixing the short filaments of the heat-spreading film with a carbonizable polymer solution to obtain a mixed solution; Introducing the mixed solution into a preset vertically arranged mold until the mixed solution solidifies to obtain a mixed solution solidified product; The solidified product of the mixed liquid is sequentially subjected to low temperature pretreatment, medium temperature carbonization treatment and high temperature graphitization treatment to obtain a density of 0.1-1.0 g / cm 3 square blocks; The graphitized square block is cut into thermal interface materials with a thickness between 0.01 mm and 10 mm.

2. The preparation method according to claim 1, characterized in that: The method of cutting the graphite-based heat-spreading film into short heat-spreading film filaments according to predetermined parameter conditions includes: Selecting one or more mixtures of artificial graphite film, graphene soaking film, and natural graphite film as the graphite soaking film; Cut the graphite heat spreader film into heat spreader film wires with a width of 10um-1000um and a length of 5-5000cm; The heat-spreading film wire is cut into short heat-spreading film wires with a length of 0.5 cm-5 cm.

3. The preparation method according to claim 2, characterized in that: The method of selecting one or more mixtures of artificial graphite film, graphene soaking film and natural graphite film as the graphite soaking film comprises: One or more mixtures of artificial graphite film, graphene heat spreader film, and natural graphite film with a heat spreader thickness of 5-100um and a density of 0.4-2.26g / cm2 are selected as the graphite heat spreader film.

4. The preparation method according to claim 1, characterized in that: The step of mixing the short filaments of the heat-spreading film with a carbonizable polymer solution to obtain a mixed solution comprises: The short filaments of the heat-spreading film are added into the polymer solution and suspended in the polymer solution to form a carbonizable and graphitizable polymer mixed solution.

5. The preparation method according to claim 4, characterized in that: The step of adding the heat-spreading film filaments into the polymer solution and suspending them in the polymer solution to form a carbonizable and graphitizable polymer mixed solution comprises: mixing the heat-spreading film filaments into a polymer solution or multiple mixed polymer solutions in a polyimide solution or a polyacrylonitrile solution to form a carbonizable and graphitizable polymer mixed solution.

6. The preparation method according to claim 1, characterized in that: The step of introducing the mixed solution into a preset vertically arranged mold until the mixed solution is solidified to obtain a mixed solution solidified product comprises: The mixed solution is introduced into a vertically arranged wooden mold, or a carbonized and graphitized polymer mold, or a graphite mold, until the mixed solution is solidified to obtain a mixed solution solidified product.

7. The preparation method according to claim 1 or 6, characterized in that: The step of introducing the mixed solution into a preset vertically arranged mold until the mixed solution is solidified to obtain a mixed solution solidified product comprises: The mixed solution is introduced into a vertically arranged mold with a cavity size of 10-100um and a depth of 10mm-5000mm until the mixed solution is solidified, wherein the width and length of the mold are both between 10mm-10000mm.

8. The preparation method according to claim 1, characterized in that: The mixed liquid solidified product is sequentially subjected to low temperature pretreatment, medium temperature carbonization treatment and high temperature graphitization treatment to obtain a density of 0.1-1.0 g / cm 3 A square block, including: The solidified mixed solution is subjected to reduction pretreatment in a low temperature environment of 200-600° C. until it is reduced from the mold; wherein the heating rate of the reduction pretreatment is controlled at 0.05° C. / min-1° C. / min, and the holding time is controlled at 30 min-360 min; The mixed solution after reduction pretreatment is subjected to carbonization treatment in a medium temperature environment of 600-1600° C. to obtain a graphite block; wherein the heating rate of the carbonization treatment is controlled at 1° C. / min-5° C. / min, and the holding time is controlled at 30min-360min; The graphite block is subjected to graphitization treatment in a high temperature environment of 2000°C-3000°C to obtain a density of 0.1-1.0 g / cm 3 , and inside it is a square block with a vertically arranged array of heat-spreading membrane wires.

9. The preparation method according to claim 1, characterized in that: The step of cutting the graphitized square block into thermal interface materials with a thickness between 0.01 mm and 10 mm comprises: The graphitized blocks are cut vertically to obtain thermal interface materials with a thickness between 0.01 mm and 10 mm.

10. The preparation method according to claim 9, characterized in that: The graphitized block is vertically cut to obtain a thermal interface material with a thickness between 0.01 mm and 10 mm, comprising: The graphitized square block with a vertically arranged heat-dissipating membrane wire array is cut vertically to obtain a square block with a thickness of 0.01 mm to 10 mm and a density of 0.1 to 1.0 g / cm 3 The vertical thermal conductivity is 90-150W*m -1 K -1 Thermal interface materials.

11. A thermal interface material, characterized in that: The thermal interface material has a density of 0.1-1.0 g / cm 3 , thickness is 0.01mm-10mm, and its vertical thermal conductivity is 90-150W*m -1 K -1 , which is prepared by the preparation method described in any one of claims 1 to 10 above.